If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 282 + -3x = 42x + -22 Reorder the terms: 282 + -3x = -22 + 42x Solving 282 + -3x = -22 + 42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42x' to each side of the equation. 282 + -3x + -42x = -22 + 42x + -42x Combine like terms: -3x + -42x = -45x 282 + -45x = -22 + 42x + -42x Combine like terms: 42x + -42x = 0 282 + -45x = -22 + 0 282 + -45x = -22 Add '-282' to each side of the equation. 282 + -282 + -45x = -22 + -282 Combine like terms: 282 + -282 = 0 0 + -45x = -22 + -282 -45x = -22 + -282 Combine like terms: -22 + -282 = -304 -45x = -304 Divide each side by '-45'. x = 6.755555556 Simplifying x = 6.755555556
| 8t^2-4t^3=-60t | | x+y=160 | | -4+6(x-5)=12x+6-6x | | 0=1+2+3(21+30+4M) | | N-7=21 | | 2x+2=3x-2/7 | | (7x+35)/(2)((1)/(x+5)) | | 0=1+2+3(7N+30+4M) | | 0.50x+1.10y=22.00 | | N*9=27 | | -9x+4y=-3 | | 13x+8=14x-8 | | 2+3x=2+8x | | 2cosx*sinx=0 | | 0=3(7N+30+4M) | | -8-8x=104-29x | | 4+2+-1+-3= | | 10b-4=44 | | 5+3x=2+8x | | 3x(x+1)=42 | | 5+3x=2+10x | | 30-7c=10c-4 | | 5+3x=2+6x | | 3/4x+26=18 | | 4x-5x^2/x | | 2x-3(1)=-7 | | 26-3/4x=18 | | 5-3x=84+6x | | 12+14=3*f | | 5-3x=4+6x | | 6-8(5-3x)=0 | | 52+g=45+11 |